Interactive electrical behaviour in mormyrid weakly electric fish: jamming avoidance response or social interaction? - Nils Weimar; Moritz Maxeiner; Emily M. Wong; Ingolf P. Rick; Mathis Hocke; Tim Landgraf; Gerhard von der Emde (Animal Behaviour, 2025)

Honey bee drones are synchronously hyperactive inside the nest - Louisa C. Neubauer; Jacob D. Davidson; Benjamin Wild; David M. Dormagen; Tim Landgraf; Iain D. Couzin; Michael L. Smith (Animal Behaviour, 2023)

Electric signal synchronization as a behavioural strategy to generate social attention in small groups of mormyrid weakly electric fish and a mobile fish robot - Martin Worm; Tim Landgraf; Gerhard von der Emde (Biological Cybernetics, 2021)
African weakly electric fish communicate at night by constantly emitting and perceiving brief electrical signals (electric organ discharges, EOD) at variable inter-discharge intervals (IDI). While the waveform of single EODs contains information about the sender’s identity, the variable IDI patterns convey information about its current motivational and behavioural state. Pairs of fish can synchronize their EODs to each other via echo responses, and we have previously formulated a ‘social attention hypothesis’ stating that fish use echo responses to address specific individuals and establish brief dyadic communication frameworks within a group. Here, we employed a mobile fish robot to investigate the behaviour of small groups of up to four Mormyrus rume and characterized the social situations during which synchronizations occurred. An EOD-emitting robot reliably evoked social following behaviour, which was strongest in smaller groups and declined with increasing group size. We did not find significant differences in motor behaviour of M. rume with either an interactive playback (echo response) or a random control playback by the robot. Still, the robot reliably elicited mutual synchronizations with other fish. Synchronizations mostly occurred during relatively close social interactions, usually when the fish that initiated synchronization approached either the robot or another fish from a distance. The results support our social attention hypothesis and suggest that electric signal synchronization might facilitate the exchange of social information during a wide range of social behaviours from aggressive territorial displays to shoaling and even cooperative hunting in some mormyrids.

A neural network model for familiarity and context learning during honeybee foraging flights - Jurek Müller; Martin Nawrot; Randolf Menzel; Tim Landgraf (Biological Cybernetics, 2018)